WR 35a: A new double-lined spectroscopic binary - Gamen, Roberto Claudio (2014)
Aims. We present the first orbital solution for the Wolf-Rayet star, WR 35a, that was discovered by a spectroscopic monitoring of faint WN-type stars. Methods. Spectral features of two different components were identified, and thus a method of disentangling the individual spectra of both components was applied. Radial velocities were determined for each component in the binary system. Results. The orbital solution and component properties of the system were derived. We determined that WR 35a is composed of a WN6 star with a O8.5 V companion orbiting at a 41.90-day period.